Laporan Kasus Penyakit Tetanus pada Kambing Peranakan Etawa di Desa Penjalinan, Tulungagung: CASE REPORT OF TETANUS IN ETAWA CROOSBREED GOATS IN PENJALINAN VILLAGE, TULUNGAGUNG - Jannah, Aeliyyah Nur (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2023)
A - 7 month old female etawa belongs to Mr. Joko It shows that has problems of difficulties of opening it's mouth and soundless for three days. The physical check is carried out through palpalis from goat's nails, legs, and in the mouth area. The result of physical checks found that the goat could not open it's mouth and got pain while touching it. In the mouth area has scars. It indicates that the goat has spesial tetanus., this indicates that the goat was diagnosed with tetanus, where the characteristic symptom seen is jaw lock—providing supportive therapy such as Xylazine as a muscle relaxant, penicillin antibiotics, and vitamin B complex. Curative treatment such as antitoxin is still scarce in livestock, especially in goat farms in Indonesia.